2016
DOI: 10.1002/hep.28548
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of lethal‐7b and miR‐125a/b Maturation by Lin28b Enables Maintenance of Stem Cell Properties in Hepatoblasts

Abstract: In liver development, hepatoblasts that act as hepatic stem/progenitor cells proliferate and differentiate into both hepatocytes and cholangiocytes to form liver tissues. Although numerous factors contribute to this event, little is known about the roles of microRNAs in hepatoblast proliferation and differentiation. In this study, we focused on the lineage-28 (Lin28) family proteins, which are required for microRNA regulation in pluripotent stem cells and cancer cells, and investigated their roles as regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 50 publications
1
33
0
Order By: Relevance
“…Previous studies have shown that miR-125a plays a tumor-suppressive role in various cancers through negatively regulating tumor oncogenes 3336 . For example, miR-125a was found to be an independent prognostic factor and inhibit proliferation of gastric cancer 37 and miR-125a function as tumor suppressor by regulating abnormal activity of SIRT7 in human HCC tumorigenesis 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that miR-125a plays a tumor-suppressive role in various cancers through negatively regulating tumor oncogenes 3336 . For example, miR-125a was found to be an independent prognostic factor and inhibit proliferation of gastric cancer 37 and miR-125a function as tumor suppressor by regulating abnormal activity of SIRT7 in human HCC tumorigenesis 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, signaling pathways that regulate the LPCs/CSCs fate have been suggested, such as bone morphogenetic protein (BMP), fibroblast growth factor (FGF), Wnt, oncostatin M (OSM), TGF-β, Jagged1/Notch, IL-6/STAT3, and hepatocyte growth factor (HGF)/c-Met [3, 31]. Moreover, expression patterns of miRNAs in EpCAM + hepatic CSCs differ from that in LPCs, and miRNAs such as Let-7 family members, miR-125a/b and miR-452 are also involved in determination and maintenance of LPCs/CSCs [7981]. It is worth noting that a series of intriguing questions have not been addressed.…”
Section: Cancer Stem Cells and Inflammation Nichementioning
confidence: 99%
“…Today, it is present in all animals with bilateral symmetry and its nucleotide sequence is very well conserved, with an 11 nucleotide stretch encompassing the seed region that is identical in all species analyzed [24]. This microRNA plays a fundamental role in downregulating Lin-28 protein, thus promoting phase transitions in development and/or cell differentiation in nematodes, insects and mammals [3639]. In mammalians, miR-125a appears to be expressed in most tissues, mainly targeting membrane receptors or intracellular signal transductors of mitogenic signals, thus limiting cell proliferation.…”
Section: Discussionmentioning
confidence: 99%